Winston of Churchill : one bear's battle against global warming - Okimoto, Jean Davies (Sasquatch Books, 2007)
Winston is worried because the ice of the Hudson Bay is melting sooner each year and he and his fellow polar bears have less time to hunt for food, but he comes up with an idea that will make the tourists who come to see the bears realize what is going on.